Diet Quality and All-Cause and Cancer-Specific Mortality in Older Adults with Invasive Cancer: The Multiethnic Cohort Study. (29th May 2020) - Park, Song-Yi; Shvetsov, Yurii; Kang, Minji; Setiawan, V Wendy; Boushey, Carol; Wilkens, Lynne; Marchand, Loïc Le
Abstract: Objectives: We examined the association of postdiagnostic diet quality with all-cause and cancer-specific mortality in older adults diagnosed with invasive cancer, in comparison with those without invasive cancer, in the Multiethnic Cohort. Methods: Data were from 66, 374 African American, Native Hawaiian, Japanese American, Latino, and White men and women, who had no prevalent cancer, heart disease, or stroke at baseline (1993–1996, 45–75 years) and completed a quantitative food frequency questionnaire at both baseline and 10-year follow-up (2003–2007). Overall diet quality was measured by the Healthy Eating Index (HEI)-2015, the Alternative HEI-2010 (AHEI-2010), the alternate Mediterranean Diet (aMED), and the Dietary Approaches to Stop Hypertension (DASH) scores. Invasive cancer cases between the baseline and 10-year surveys and deaths after the 10 year survey were identified through linkage to cancer registries and to state death files and the National Death Index. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated in multivariate Cox models for the dietary indexes at 10-year follow-up with subsequent mortality. Results: Age-adjusted mean scores of the 4 dietary indexes at baseline (prediagnosis) and 10-year follow-up (postdiagnosis) were similar or slightly lower in participants with cancer (n = 5998), compared to those without cancer (n = 60, 376). Among participants with cancer (71.5 ± 8.0 years), 2006 all-cause and 1005 cancer-specific deaths were identified during a mean follow-up of 8 years after the 10-year survey. Postdiagnostic scores from all 4 indexes were associated with lower risk of all-cause and cancer mortality: for the highest vs. lowest quartiles, HR (95% CI) for all-cause mortality was 0.72 (0.62–0.82) for HEI-2015, 0.84 (0.73–0.96) for AHEI-2010, 0.74 (0.63–0.86) for aMED, and 0.76 (0.66–0.87) for DASH. The corresponding HRs (95% CIs) for cancer mortality were 0.81 (0.66–0.99), 0.81 (0.66–0.99), 0.72 (0.58–0.89), and 0.79 (0.65–0.97). These HRs were similar to those for participants without cancer. Conclusions: Postdiagnostic high-quality diet was related to lower all-cause and cancer mortality in older adults with invasive cancer, with risk reduction comparable to that among participants without cancer. Funding Sources: National Cancer Institute.